Incorporation And Exploration Of Local Imageries And Identities In Malaysia's Graffiti Art - Sarena Abdullah; Norshahidan Mohamad (ITB Journal Publisher, LPPM ITB, 2015)
The production of graffiti art in Malaysia can be traced back to the late 1990's. Since then, graffiti art has beenembraced by local municipalities as well as the National Visual Art Gallery (NVAG) in their public programming and activities. Despite these positive developments, how the local graffiti artists infused local imageries and indentities in their work had not been examined. The parallels between graffiti art practices and the development of modern art in Malaysia, made the emergence of forms and themes that reflect local identity in graffiti art not a surprise, as these were also the inherent issues explored by local artists in the domain of fine arts. This paper hence, discusses the different approaches taken by Malaysia's graffiti artists, how they incorporate and explored their visual ideas rooted in hip hop culture and the New York City Subway graffiti, with local imageries and identities. This paper will also discuss the history and background of Malaysia's graffiti art as well as how Malaysian graffiti artists employedvarious local imageries and identity.Keywords: graffiti art; local identities; Malaysian graffiti art; urban culture.